The mental health needs of child and adolescent refugees and asylum seekers entering Europe - Supakyada Sapthiang; William Van Gordon; Edo Shonin; Mark D Griffiths (Social Health and Behavior, 2019)
Children and adolescents constitute more than half of the global refugee population, and almost one-third of first-time asylum seekers in the European Union (EU) during 2015 were under 18 years of age. Syria, in particular, accounts for a substantial proportion of young refugees and asylum seekers because the ongoing civil war has led to almost 5 million Syrians fleeing their country and becoming refugees during the past 7 years. Being a child or adolescent refugee or asylum seeker carries an increased risk of developing mental illness, and such displaced young people are known to experience problems in accessing health-care support. The present article draws on examples from Syria in order to (i) Highlight mental health issues that typically arise in children and adolescent refugees and asylum seekers entering Europe and (ii) discuss how changes to health systems and policies in European countries receiving refugees and asylum seekers can be better aligned with global efforts to improve the mental health of young displaced immigrants. In general, research findings indicate that there is a need for better awareness, intra-agency collaboration, and cultural sensitivity toward the mental health needs of this immigrant population. Furthermore, there is also a need for EU countries to better respond to posttraumatic stress disorder and other typical refugee and asylum seeker mental health problems by more closely aligning national policies with global initiatives to improve the mental health of young displaced immigrants.